The Posterior Arm Flap for Reshaping the Postbariatric Breast - Vincenzo Vindigni, MD, PhD; Paolo Marchica, MD; Andrea Pagani, MD; Franco Bassetto, MD, PhD; Tito Brambullo, MD (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. Postbariatric surgery, either by itself or in association with other procedures, tries to correct physical defects and body deformities. Because of the intrinsic complexity of massive weight loss (MWL) patients, more than a single procedure is, most of the time, required. We report a combined surgical method able to improve arms’ and breasts’ contour that aims to obtain a satisfying functional and aesthetic result by reducing surgical times and costs.